Patterns and determinants of breastfeeding and complementary feeding practices in urban informal settlements, Nairobi Kenya - Mutua Martin K; Gitau Tabither M; Kyobutungi Catherine; Fotso Jean-Christophe; Madise Nyovani J; Kimani-Murage Elizabeth W; Yatich Nelly (BMC, 2011)
Abstract Background The World Health Organisation (WHO) recommends exclusive breastfeeding during the first six months of life for optimal growth, development and health. Breastfeeding should continue up to two years or more and nutritionally adequate, safe, and appropriately-fed complementary foods should be introduced at the age of six months to meet the evolving needs of the growing infant. Little evidence exists on breastfeeding and infant feeding practices in urban slums in sub-Saharan Africa. Our aim was to assess breastfeeding and infant feeding practices in Nairobi slums with reference to WHO recommendations. Methods Data from a longitudinal study conducted in two Nairobi slums are used. The study used information on the first year of life of 4299 children born between September 2006 and January 2010. All women who gave birth during this period were interviewed on breastfeeding and complementary feeding practices at recruitment and this information was updated twice, at four-monthly intervals. Cox proportional hazard analysis was used to determine factors associated with cessation of breastfeeding in infancy and early introduction of complementary foods. Results There was universal breastfeeding with almost all children (99%) having ever been breastfed. However, more than a third (37%) were not breastfed in the first hour following delivery, and 40% were given something to drink other than the mothers' breast milk within 3 days after delivery. About 85% of infants were still breastfeeding by the end of the 11th month. Exclusive breastfeeding for the first six months was rare as only about 2% of infants were exclusively breastfed for six months. Factors associated with sub-optimal infant breastfeeding and feeding practices in these settings include child's sex; perceived size at birth; mother's marital status, ethnicity; education level; family planning (pregnancy desirability); health seeking behaviour (place of delivery) and; neighbourhood (slum of residence). Conclusions The study indicates poor adherence to WHO recommendations for breastfeeding and infant feeding practices. Interventions and further research should pay attention to factors such as cultural practices, access to and utilization of health care facilities, child feeding education, and family planning.